Two-Year Breastfeeding in the Qur'an as a Stunting Prevention Strategy in Indonesia - Khairun Nisa Amci Ilzania; Derysmono; Fahmi Rusdi Toha; Akhmad Nizaruddin; Dia Hidayati Usman (Jurnal Ilmu Pendidikan dan Sains Islam Interdisipliner, 2026)
Stunting is not merely a problem of short stature; it reflects chronic nutritional deprivation, repeated infection, and inadequate care during the decisive stages of child growth. This article adapts and translates a qualitative library-based study on the Qur'anic guidance of two-year breastfeeding as a preventive framework for stunting in Indonesia. Using a thematic tafsir approach, the study examines Qur'anic verses on rada'ah (breastfeeding), particularly Qur'an 2:233, 31:14, and 46:15, and relates them to health literature on exclusive breastfeeding, complementary feeding, and the first 1000 days of life. The discussion shows that the Qur'an presents breastfeeding as a child right, a maternal dignity, and a paternal responsibility because the father is required to support the mother materially and emotionally. Two-year breastfeeding is therefore not only a religious recommendation but also a family and public-health strategy. The article concludes that Qur'anic parenting values can strengthen stunting prevention by integrating nutrition, mental health support for mothers, father involvement, ethical health services, and community education.